2020
DOI: 10.1016/j.omtn.2019.12.025
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Circular RNA Profiling Reveals Exosomal circ_0006156 as a Novel Biomarker in Papillary Thyroid Cancer

Abstract: Circular RNAs (circRNAs) are a class of noncoding RNAs that are broadly expressed in various biological cells and function in regulating gene expression. However, the molecular mechanisms that link circRNAs with progression of papillary thyroid carcinoma (PTC) are not well understood. In the present study, the function of circ_0006156 (circFNDC3B) was investigated in human PTC cells. First, we detected the expression of circFNDC3B in PTC tissues and PTC cell lines by RT-PCR. A luciferase reporter assay and AGO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 33 publications
1
87
0
Order By: Relevance
“…Further, we found that circ-LRIG3 was also upregulated in HCC plasma, the AUC value was 0.8681 (95%CI: 0.7843 ~ 0.9519), suggesting its great potential as a non-invasive diagnostic marker of HCC. Of note, recent studies show that some circRNAs are enriched and stable in exosomes [27,28], such as hsa_circ_0051443 [29], hsa_circ_100338 [30] and hsa_circ_0006156 [31]. Whether circ-LRIG3 also exists in exosomes is worth further study, in addition, the multi-center large-scale sample investigation is necessary to con rm the diagnostic and prognostic value of circ-LRIG3 in HCC.…”
Section: Discussionmentioning
confidence: 98%
“…Further, we found that circ-LRIG3 was also upregulated in HCC plasma, the AUC value was 0.8681 (95%CI: 0.7843 ~ 0.9519), suggesting its great potential as a non-invasive diagnostic marker of HCC. Of note, recent studies show that some circRNAs are enriched and stable in exosomes [27,28], such as hsa_circ_0051443 [29], hsa_circ_100338 [30] and hsa_circ_0006156 [31]. Whether circ-LRIG3 also exists in exosomes is worth further study, in addition, the multi-center large-scale sample investigation is necessary to con rm the diagnostic and prognostic value of circ-LRIG3 in HCC.…”
Section: Discussionmentioning
confidence: 98%
“…Further, we found that circ-LRIG3 was also upregulated in HCC plasma, the AUC value was 0.8681 (95%CI: 0.7843 ~ 0.9519), suggesting its great potential as a non-invasive diagnostic marker of HCC. Of note, recent studies show that some circRNAs are enriched and stable in exosomes [ 26 , 27 ], such as hsa_circ_0051443 [ 28 ], hsa_circ_100,338 [ 29 ] and hsa_circ_0006156 [ 30 ]. Whether circ-LRIG3 also exists in exosomes is worth further study, in addition, the multi-center large-scale sample investigation is necessary to confirm the diagnostic and prognostic value of circ-LRIG3 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, Prdm16 activates transcriptional cofactors and drives brown adipocyte development, while Ucp1 is crucial for thermogenesis against cold and obesity [115][116][117]. In addition, exosomes exert specific functions in mediating signaling transduction between neighboring or distant cells by delivering circRNAs [118,119] (Fig. 2F).…”
Section: Circrna_0010522mentioning
confidence: 99%